Traces of Greek Mythology in the Folk Music and Oral Literature of Bushehr - Seyed Mohammadreza Beladi (Asian-European Music Research Journal, 2023)
This article examines parts of the oral literature and music of Bushehr, a port city in southern Iran. There is a song in Bushehr's music that uses words like helleh (heːlle̞) and heliosa (heːlijosa), that have no meaning for the people of Bushehr. This paper suggests that the origin of these words goes back to Greek mythology and that they are the remains of hymns or spells recited in praise of Helios and other ancient gods. To this end, in addition to qualitative and field research, extensive historical studies were carried out, focusing on the Hellenistic period after the conquest of Iran by Alexander the Great. I suggest that although the evolution of music in Bushehr was influenced by the military domination of Greece through acculturation, the cultural background of Bushehr was not ineffective in accepting this. As a result, assimilation occurred, and some mythical elements of Greece were localised in Bushehr.